2020
DOI: 10.1007/s00192-020-04274-9
|View full text |Cite
|
Sign up to set email alerts
|

Is endoanal, introital or transperineal ultrasound diagnosis of sphincter defects more strongly associated with anal incontinence?

Abstract: Introduction and hypothesis Our aim was to explore the association between anal incontinence (AI) and persistent anal sphincter defects diagnosed with 3D endoanal (EAUS), introital (IUS) and transperineal ultrasound (TPUS) in women after obstetric anal sphincter injury (OASI) and study the association between sphincter defects and anal pressure. Methods We carried out a cross-sectional study of 250 women with OASI recruited during the period 2013-2015. They were examined 6-12 weeks postpartum or in a subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
(67 reference statements)
0
19
0
Order By: Relevance
“…We have shown previously using EAUS that, in the immediate postnatal period and in a subsequent pregnancy, anal incontinence symptoms and anal manometry (which correlate with anal sphincter function) are significantly worse in women with an anal sphincter defect > 30 • in comparison to those with smaller defects 6 . Moreover, we found that, in comparison to TPUS, EAUS has the strongest association with anal incontinence symptoms up to 2 years following OASI 7 . The take-home message of our study 1 is that the defect angle measurement obtained on EAUS is not equivalent to that of TPUS for the same reason acknowledged by Dietz and Shek, namely, that EAUS distends the anal canal.…”
mentioning
confidence: 63%
“…We have shown previously using EAUS that, in the immediate postnatal period and in a subsequent pregnancy, anal incontinence symptoms and anal manometry (which correlate with anal sphincter function) are significantly worse in women with an anal sphincter defect > 30 • in comparison to those with smaller defects 6 . Moreover, we found that, in comparison to TPUS, EAUS has the strongest association with anal incontinence symptoms up to 2 years following OASI 7 . The take-home message of our study 1 is that the defect angle measurement obtained on EAUS is not equivalent to that of TPUS for the same reason acknowledged by Dietz and Shek, namely, that EAUS distends the anal canal.…”
mentioning
confidence: 63%
“…Its most common clinical indication is the assessment of sphincter integrity following obstetric trauma. It is the reference standard for imaging of the anal sphincters and diagnosis of sphincter defects and correlates with symptoms and histological diagnosis [ 53 ]. Translabial/transperineal approach overcomes the limitations of endovaginal and transrectal techniques providing minimal pressure on local structures and it is least likely to alter surrounding anatomy.…”
Section: Investigationsmentioning
confidence: 99%
“…Three dimensional images of the sphincter complex were studied across three levels of 'high', 'mid' and 'low' as per the Liverpool Ultrasound Pictorial chart (LUPIC) [15]. Defects in the muscles of the EAS or IAS were identified as those exceeding 1 hour (>30 degrees) [16] on a clock face.…”
Section: Methodsmentioning
confidence: 99%